Immunohistochemical evaluation of FHIT and WWOX expression in normal oral mucosa, oral epithelial dysplasia and oral squamous cell carcinoma - Majbil, Dhaffar A; Merza, Muna S (Journal of Baghdad College of Dentistry, 2014)
Background: Oral squamous cell carcinoma is the most prevalent malignant neoplasm of the oral cavity which results from accumulated genetic and epigenetic alterations. It is not always inexorable and may be reversible if early intervention in the process can occur to prevent further genetic mutation and disease progression. The FHIT gene is a tumor suppressor gene located in FRA3B region which is the most active common fragile site, where DNA damage leading to aberrant transcripts and translocations frequently occur. The WWOX is a tumor suppressor gene that plays a central role in tumor suppression through transcriptional repression and apoptosis, with its apoptotic function the more prominent of the two. This study aimed to evaluate and compare the immunohistochemical expression of FHIT and WWOX in normal oral mucosa, oral epithelial dysplasia and oral squamous cell carcinoma and to correlate the expression of the mentioned markers with the clinicopathological features and to show the expression of studied markers with each other. Materials and methods: Fifty formalin-fixed, paraffin embedded tissue blocks (10 cases of normal oral mucosa, 19 cases of oral epithelial dysplasia, and 21 cases of oral squamous cell carcinoma) were included in this study. Immunohistochemical staining was performed using anti FHIT polyclonal antibody, and anti WWOX polyclonal antibody. Results: Positive IHC of FHIT was detected with high score in all cases of NOM, 16 cases (84%) of OED and 18 cases (86%) of OSCC. For WWOX expression positive IHC detected with high score in all cases (100%) of NOM, 14 cases (74%) of OED and 15 cases (71%) of OSCC. There was statistically highly significant correlation of both markers in OED and non significant correlation in OSCC, with significant differences among studied groups. Conclusions: These results signifying both markers cooperative tumor suppressive role and potential pathological transition from normal oral mucosa to dysplastic epithelium and subsequently cause malignant oral lesions.